Memory - Papers Read at the Jewish and Christian Perspectives Conference, Utrecht 2022 - Ackerman, Ari,; Hoopen, Robin B. ten,; Teugels, Lieve M.,; Wieringen, Archibald L.H.M. van, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Memory - Papers Read at the Jewish and Christian Perspectives Conference, Utrecht 2022 connects past, present, and future. This conference volume demonstrates the diversity of 'memory' in the Jewish and Christian traditions. 'Memory' turns out to be a key to investigating and better understanding many aspects of Judaism and Christianity, including their mutual relationship. In these traditions, memory is not simply about recalling events, but about preserving identity, culture, and divine teachings. The act of remembering is central to how communities pass down their religious beliefs, laws, and moral frameworks across generations. It also plays a role in communal cohesion, ensuring that the experiences of the fathers and their wisdom would not get lost, but rather actively re-lived and celebrated.